Ladrill Market Dynamics And Economic Growth : Evidence From Emerging Markets - Natsir, Imron; Zainuddin, Yusran; Sari, Yolanda; Zainudin, La Ode (Nomico, 2024)
Labor market dynamics and economic growth are two key components that are interrelated in determining the stability and economic progress of a country. In emerging markets, significant changes in the labor market can affect the overall economic growth path. This research analyzes the relationship between labor market dynamics and economic growth in emerging markets. Using a literature study method, this study collected data from various secondary sources including academic journals, policy reports and relevant case studies during the period 2000-2023. Thematic analysis is used to explore labor market indicators such as the labor force participation rate, unemployment rate, and real wages, and their relationship to Gross Domestic Product (GDP) growth. The research results show that increasing labor force participation and decreasing unemployment rates significantly contribute to economic growth in emerging markets. Additionally, increases in real wages were found to have a positive effect on labor productivity and economic competitiveness. These findings highlight the importance of inclusive and sustainable labor market policies to promote stable economic growth in developing countries. Policy implications and further recommendations are discussed to support effective decision making by policy makers.